2010
DOI: 10.1007/s10826-009-9345-z
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Parental Knowledge as Moderators of the Relation Between Parental Psychological Control and Relational and Physical/Verbal Aggression

Abstract: Previous research demonstrates that aspects of parenting interact to influence child adjustment. We aimed to extend this research by examining parenting strategies associated with behavioral control, specifically sources of parental knowledge regarding child behavior (child disclosure, parental solicitation, parental control), as moderators of the relation between psychological control and relational and physical/verbal aggression. Our sample included 89 children (56% male), ages 9-12. Consistent with prior re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 38 publications
0
15
0
3
Order By: Relevance
“…That is, because adolescents are striving for increasing levels of autonomy as they get older (Smetana, 2000), they may prefer to control the flow of information to their parents. Furthermore, instead of being viewed by the youth as a sign of concern and interest, parental solicitation may be viewed as intrusive by the youth (e.g., Gaertner et al, 2010). Thus, parents’ active efforts to gather information about their adolescents may either have no discernible impact on youth adjustment (as indicated by the current study), or these efforts may be related to poor outcomes, especially among older youth.…”
Section: Discussionmentioning
confidence: 99%
“…That is, because adolescents are striving for increasing levels of autonomy as they get older (Smetana, 2000), they may prefer to control the flow of information to their parents. Furthermore, instead of being viewed by the youth as a sign of concern and interest, parental solicitation may be viewed as intrusive by the youth (e.g., Gaertner et al, 2010). Thus, parents’ active efforts to gather information about their adolescents may either have no discernible impact on youth adjustment (as indicated by the current study), or these efforts may be related to poor outcomes, especially among older youth.…”
Section: Discussionmentioning
confidence: 99%
“…Nelson et al's (2008) study highlights the complex nature of linkages between child and parent social cognition and children's relationally aggressive behavior with peers. Their findings suggest that mothers might directly transmit a hostile attributional style to children, perhaps via everyday conversations about peer interactions (see Barrett et al, 1996), whereas fathers who make hostile attributions might use parenting practices that more directly model relationally aggressive actions, such as psychological control (e.g., Gaertner et al, 2010;Nelson, Hart, Yang, Olsen, & Jin, 2006). Nevertheless, the fact that prior research has not convincingly demonstrated that children who use relational aggression interpret ambiguous provocations in a hostile manner raises questions about the role of SIP processes for this subtype of aggression.…”
Section: The Role Of Parents' Hostile Attributions In Child Aggressionmentioning
confidence: 99%
“…Another parenting practice that may conceptually overlap with a more controlling parenting approach is psychological control, a highly restrictive and intrusive form of parenting practice that involves the parent withdrawing love from the child, inducing the child to feel guilty, and invalidating the child's feelings (Barber, 1996). Psychological control has been positively associated with problem behaviors like aggression and delinquency in previous prospective studies (e.g., Bean, Barber, & Crane, 2006;Gaertner et al, 2010;Galambos, Barker, & Alameida, 2003;Kincaid, Jones, Cuellar, & Gonzalez, 2011;Pettit, Laird, Dodge, Bates, & Criss, 2001;Taylor, Lopez, Budescu, & McGill, 2012). This parenting practice has not, however, been widely studied in relation to similar adolescent outcomes in low-income, urban, African American samples.…”
Section: Introductionmentioning
confidence: 99%